2010
DOI: 10.1177/1059840510369231
|View full text |Cite
|
Sign up to set email alerts
|

School-Located Vaccination Clinics: Then and Now

Abstract: School-located vaccination has a long history in the United States. The 2008 Advisory Committee on Immunization Practices (ACIP) recommendation for annual influenza vaccination of all children 6 months through 18 years of age adds approximately 30 million individuals to the overall cohort recommended to have a yearly vaccination. The ability to administer this vast number of vaccinations may be beyond the capacity of primary care providers, leaving schools as an attractive venue for mass immunization clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…A literature review identified several SLV programs held in the United States, with some programs having been conducted over multiple years (Hull & Ambrose, 2011). These programs were organized at either the state or local level (Effler et al, 2010; Hull, 2010; Hull, Frauendienst, Gundersen, Monsen, & Fishbein, 2008; King et al, 2006; Mazyck, 2010; Schmier, Li, King, Nichol, & Mahadevia, 2008). Also, during the 2009–2010 H1N1 pandemic influenza season, SLV clinics were widely held across the United States to vaccinate school-age children, one of the initial target groups for 2009 H1N1 influenza vaccination (Centers for Disease Control and Prevention, 2009; Hull & Ambrose, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review identified several SLV programs held in the United States, with some programs having been conducted over multiple years (Hull & Ambrose, 2011). These programs were organized at either the state or local level (Effler et al, 2010; Hull, 2010; Hull, Frauendienst, Gundersen, Monsen, & Fishbein, 2008; King et al, 2006; Mazyck, 2010; Schmier, Li, King, Nichol, & Mahadevia, 2008). Also, during the 2009–2010 H1N1 pandemic influenza season, SLV clinics were widely held across the United States to vaccinate school-age children, one of the initial target groups for 2009 H1N1 influenza vaccination (Centers for Disease Control and Prevention, 2009; Hull & Ambrose, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Schools have been proposed as a potentially viable venue to reach school-age children for vaccinations routinely recommended for children and adolescents, including influenza vaccination (Lindley et al, 2008; Mazyck, 2010). School-located vaccination (SLV) clinics are defined as clinics designed to vaccinate school-age children.…”
Section: Introductionmentioning
confidence: 99%
“…The 2009 H1N1 season afforded innumerable opportunities to implement mass immunization clinics that were also school based (CDC, 2009a; Jenlink et al, 2010a; Mazyck, 2010). While some clinics were very successful in immunizing multiple students and community members in a short period of time, however, other clinics also required a significant amount of time for planning to include extensive resources for manpower (Mazyck, 2010) and funding (Jenlink et al, 2010a). Nevertheless, many school-based immunization clinics throughout the United States successfully vaccinated hundreds of thousands of children in the fall of 2009 against H1N1 (CDC, 2010a; Jenlink et al, 2010a; Robinson, 2010; University of Michigan, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As such, school nurses often have an important role in immunization efforts with this population (Mazyck, 2010). ''As the primary health professional in schools .…”
mentioning
confidence: 99%
See 1 more Smart Citation